How Signifying Practices Constitute Food (In)security: The Case of the Democratic People's Republic of Korea - David Shim (German Institute of Global and Area Studies (GIGA), 2010)
This paper argues that the question of food (in)security in the Democratic People's Republic of Korea is not necessarily indicative of the country's actual nutritional conditions but is rather constituted through meaning-making behavior-signifying practices-predominantly on the part of humanitarian aid institutions working there. The argument is not intended to gloss over the food and nutritional situation in North Korea or to suggest that famine, starvation, or malnutrition do not exist. The paper nevertheless argues that humanitarian institutions are not external to or separate from the reality they observe, monitor, and measure, but are rather constitutive of the categories which produce that reality - in this case food (in)security in North Korea. The undertaking of nutrition surveys, food security assessments, and food-aid monitoring as well as the issuing of consensus statements are examples of aid practices that signify North Korea in terms of vulnerability, emergency, and food insecurity. The paper's central argument is that it is through precisely these observations, assessments, and representations that food (in)security in North Korea comes into being. – – In dem Arbeitspapier wird argumentiert, dass Ernährungs(un)sicherheit in der Demokratischen Volksrepublik Korea nicht unbedingt die realen Ernährungsbedingungen des Landes widergespiegelt, sondern durch Praktiken der Signifikation - überwiegend durch humanitäre Hilfsorganisationen - konstituiert wird. Diese Argumentation soll jedoch nicht die allgemeine Ernährungssituation in Nordkorea verharmlosen. Es wird auch nicht behauptet, dass Hunger, Unterernährung oder Mangelernährung nicht existierten oder dass Hilfsorganisationen ebenjene Phänomene bewusst erfänden oder herbeiführten. Vielmehr geht es darum, aufzuzeigen, dass humanitäre Akteure nicht außerhalb der Realität stehen, die sie beobachten, vermessen und erfahren, sondern konstituierend sind für jene Kategorien, die diese Realität herstellen - im vorliegenden Fall die Ernährungs(un)sicherheit in Nordkorea. Humanitäre Hilfe umfasst bestimmte Bedeutung generierende Praktiken wie z.B. Untersuchungen der Ernährungssicherheit, Überwachung der Lebensmittelhilfe, Erklärungen über die Ernährungssituation, die Nordkoreas Ernährungslage als vulnerabel, unzureichend und unsicher darstellen. Das Arbeitspapier veranschaulicht wie durch ebenjene Praktiken die Ernährungs(un)sicherheit Nordkoreas erst entsteht.
Keywords: 300; North Korea; food security; discourse; representation; knowledge; humanitarian institutions; Nahrungsmittelhilfe; Ausländisch; Nahrungsmittelversorgung; Nordkorea